THE EFFECTIVENESS OF IMPLEMENTING INFORMATION AND COMMUNICATION TECHNOLOGY ON STUDENT ACADEMIC SERVICES (A Case Study in Bandung Institute of Technology for the 2015-2016 Period) - Supriadi, Dedi; Sa’ud, Udin Syaefudin (International Journal of Education, 2017)
The implementation of Information and Communication Technology (ICT) in higher education institutions plays an important role in realizing the competitive advantage, especially in the realization of the three pillars of higher education. In order for the implementation of ICT in higher education institutions to be effective, adequate support from infrastructure, human resources, and leader and organizational commitment is needed. The research focuses on and aims to describe the effectiveness of ICT implementation in student academic services, covering ICT policies and programs, ICT implementation strategies, ICT implementation, and the effectiveness of ICT implementation in student academic services. In addition, it attempts to formulate a hypothetical model of ICT implementation in student academic services. The research adopted the analytical-descriptive method through qualitative approach. Data were collected through interviews, observations, and documentary analysis. Afterwards, the data were analyzed through data reduction, data display, inference drawing, and verification. The research took place in Bandung Institute of Technology. The findings show that: The ICT policies and programs are based on the implementation of the three pillars of higher education (education, research, and community service); the strategies give emphasis on coordination patterns; ICT implementation in academic services is realized through e-learning (online, blended learning, video conference), academic information system, and digital library; the effectiveness of the ICT implementation is analyzed based on the realization of the program at the level of unit (decision-focused approach), performance achievement (goal-oriented approach), and student satisfaction (user-oriented approach) in terms of tangibles, reliability, responsiveness, assurance, and empathy. It is recommended that ICT implementation in academic services should be able to realize the competitive advantage of the implementation of the three pillars of higher education, which is in accordance with the institution’s vision, missions, and strategic goals, supported by the availability of infrastructure, human resources, funds, managerial and organizational commitment, and periodical evaluation and monitoring.